HUBUNGAN MOTIVASI KERJA DENGAN ETOS KERJA KARYAWAN DI FAJAR OFFSET MOJOKERTO - Rahmah, Zakiyah Zulfa; Andriani, Andriani (Politeknik Bisnis Indonesia, 2024)
This research investigates the impact of work motivation on employee work ethic at Fajar Offset Printing Mojokerto. Using a quantitative approach with an associative causal design, the study explores how intrinsic factors (such as job satisfaction and personal achievement) and extrinsic factors (including salary, bonuses, and umrah rewards) influence work ethic. Data were gathered through questionnaires distributed to 40 employees who have worked at the company for over five years, selected using purposive sampling. The findings reveal a significant relationship between work motivation and work ethic, particularly in aspects like discipline and responsibility. The analysis using a simple linear regression model resulted in the equation Y = 24.352 + 0.412X, indicating that higher work motivation is associated with a stronger work ethic. The t-test showed a statistically significant result (tcount = 3.025 > ttable = 2.023), and the coefficient of determination (R² = 0.423) indicates that 42.3% of the variation in work ethic is attributed to work motivation. The study concludes that work motivation plays a vital role in improving work ethic but highlights the need to consider other contributing factors as well